Planetary mass, vegetation height and climate. Issue 5 (7th January 2019) - Stevenson, David S.
Abstract: The maximum height trees can grow on Earth is around 122–130 m. The height is constrained by two factors: the availability of water, and where water is not limiting, the pressure available to drive the column of water along the xylem vessels against the pull of gravity (cohesion tension). In turn the height of trees impacts the biodiversity of the environment in a number of ways. On Earth the largest trees are found in maritime temperate environments along the Pacific Northwest coasts of northern California and southern Oregon. These forests provide a large number of secondary habitats for species and serve as moisture pumps that return significant volumes of water to the lower atmosphere. In this work, we apply simple mathematical rules to illustrate how super-terran planets will have significantly smaller trees, with concomitant effects on the habitability of the planet. We also consider the impact of varying tree height on climate models.